2020
DOI: 10.2478/euco-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation for Renewal of Local Cultural Heritage in Rural Communities: Case Study of the Night of Legends in Latvia

Abstract: The aim of the paper is to describe the phenomenon of the Night of Legends in Latvia particularly focusing on the case of manors in Jelgava county. This event aims to preserve and promote local cultural heritage by active involvement of local community members and visitors (individuals, amateur groups, local businesses, schools, etc.). Thematic activities in manors and palaces are targeted to raise interest and cooperation, what in turn extends the tourist season. The event is organized by the Latvian Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Moreover, an innovative, accountable management mechanism has emerged [23] based on effective capacity building by residents and governments' willingness to be involved as much as possible in communities [48]. From the perspective of the private parties involved, it was found that small startups can avoid the government-business coalition and further enhance management transparency [49,52,53,77]. This should be reasonably suggested for rural cultural heritage preservation in other contexts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, an innovative, accountable management mechanism has emerged [23] based on effective capacity building by residents and governments' willingness to be involved as much as possible in communities [48]. From the perspective of the private parties involved, it was found that small startups can avoid the government-business coalition and further enhance management transparency [49,52,53,77]. This should be reasonably suggested for rural cultural heritage preservation in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning businesses in the case study villages in Europe, small local businesses were moderately present [49,51,54,55]. Small-scale, family-run businesses indicate the economic sustainability of local societies [55,56].…”
Section: A Stakeholder Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…Historic center of Riga In Latvia, incorporating cultural assets into tourism products is an inherent aspect of the tourism offer (Paula and Kaufmane, 2020). Tourism, on the other hand, both exploits and aids in the preservation of cultural and historical heritage by improving its incorporation into commodified products.…”
Section: Cultural Heritage -Latviamentioning
confidence: 99%